Бараньи астрагалы в погребальном обряде аланского населения Верхне-Салтовского археологического комплекса - Аксёнов, В.С. (Хазарский альманах, 2020)
The article is dedicated to the study of using of sheep anklebones in the burial rite of the Alanian population of the Saltovo-Mayack culture in the Seversky Donets Basin. The article describes the characteristics of 332 anklebones, which were found in 49 burial complexes of the catacomb cemetery in the village Verkhniy Saltov (Upper Saltov) by the expeditions of N.F. Sumtsov (Kharkiv Historical Museum) in 1984–2018. The collection contains almost all types and kinds of anklebones. Most artifacts are published for the fi rst time.